2010
DOI: 10.1007/s10490-010-9198-4
|View full text |Cite
|
Sign up to set email alerts
|

Can guanxi be a problem? Contexts, ties, and some unfavorable consequences of social capital in China

Abstract: Social capital, Strong-ties and weak-ties, Guanxi , Chinese context,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 75 publications
(95 reference statements)
2
74
0
2
Order By: Relevance
“…Permeability is needed to share resources, for instance through boundary spanning activities or connections, but it also has negative effects (Lin & Si, 2010;Young, Peng, Ahlstrom, & Bruton, 2003). These include possible interference in the organization, lesser autonomy and control, or limited opportunity to build a common sense of purpose (Oliver, 1993).…”
Section: Resource Dependence Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Permeability is needed to share resources, for instance through boundary spanning activities or connections, but it also has negative effects (Lin & Si, 2010;Young, Peng, Ahlstrom, & Bruton, 2003). These include possible interference in the organization, lesser autonomy and control, or limited opportunity to build a common sense of purpose (Oliver, 1993).…”
Section: Resource Dependence Theorymentioning
confidence: 99%
“…Yet these linkages also carry some costs and risks (Lin & Si, 2010). Researchers employing resource dependence theory (RDT) in particular have shown that risks are prevalent when there is a power imbalance, as powerful partners may appropriate organizational resources (Casciaro & Piskorski, 2005;Emerson, 1962;Gulati & Singh, 1998;Pfeffer & Salancik, 1978).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perspectives, review, and commentary papers are all welcome (e.g. Ismail & Ford, 2010;Lin & Si, 2010;Zhou & Peng, 2010).…”
Section: Formatting and Style; Aims And Scopementioning
confidence: 99%
“…Indeed, the recent Special Issues in APJM on corporate governance in Asia (Globerman, Peng, & Shapiro, 2011) and on managing in ethnic Chinese communities (Ahlstrom et al, 2010), provide a number of excellent examples of the variety of different papers published in APJM. These range from empirical papers to qualitative and exploratory ones, to conceptual papers, and commentaries and reviews (e.g., Dieleman, 2010;Filatotchev, Zhang, & Piesse, 2011;Globerman et al, 2011;Lin & Si, 2010;Wielemaker & Gedajlovic, 2011;Zou, Chen, & Ghauri, 2010).…”
mentioning
confidence: 99%